2010
DOI: 10.1158/0008-5472.can-10-0111
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib (YN968D1) Reverses Multidrug Resistance by Inhibiting the Efflux Function of Multiple ATP-Binding Cassette Transporters

Abstract: Apatinib, a small-molecule multitargeted tyrosine kinase inhibitor, is in phase III clinical trial for the treatment of patients with non-small-cell lung cancer and gastric cancer in China. In this study, we determined the effect of apatinib on the interaction of specific antineoplastic compounds with P-glycoprotein (ABCB1), multidrug resistance protein 1 (MRP1, ABCC1), and breast cancer resistance protein (BCRP, ABCG2). Our results showed that apatinib significantly enhanced the cytotoxicity of ABCB1 or ABCG2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
268
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(277 citation statements)
references
References 50 publications
9
268
0
Order By: Relevance
“…It was also demonstrated that PR -luminal B tumors that were treated with neoadjuvant chemotherapy (adriamycin/cyclophosphamide) (70). c Apatinib (YN968D1) is a small-molecule TKI that inhibits VEGFR2 (Flk-1/KDR), RET (rearranged during transfection), c-Kit (stem cell factor receptor) and c-Src tyrosine kinases (142). HER, human epidermal growth factor receptor; ER, estrogen receptor; EGFR, epidermal growth factor receptor; VEGFR, vascular endothelial growth factor receptor; FGF, fibroblast growth factor receptor; IGF, insulin-like growth factor; PI3K, phosphatidylinositol-3-kinase; mTOR, mammalian target of rapamycin; PDK, phosphoinositide-dependent kinase; MAPK, mitogen-activated protein kinase; PDGFR, platelet-derived growth factor receptor; FLT, FMS-like tyrosine kinase; TKI, tyrosine kinase inhibitor.…”
Section: Luminal B Subtype Breast Cancer Therapeutic Potentialsmentioning
confidence: 99%
“…It was also demonstrated that PR -luminal B tumors that were treated with neoadjuvant chemotherapy (adriamycin/cyclophosphamide) (70). c Apatinib (YN968D1) is a small-molecule TKI that inhibits VEGFR2 (Flk-1/KDR), RET (rearranged during transfection), c-Kit (stem cell factor receptor) and c-Src tyrosine kinases (142). HER, human epidermal growth factor receptor; ER, estrogen receptor; EGFR, epidermal growth factor receptor; VEGFR, vascular endothelial growth factor receptor; FGF, fibroblast growth factor receptor; IGF, insulin-like growth factor; PI3K, phosphatidylinositol-3-kinase; mTOR, mammalian target of rapamycin; PDK, phosphoinositide-dependent kinase; MAPK, mitogen-activated protein kinase; PDGFR, platelet-derived growth factor receptor; FLT, FMS-like tyrosine kinase; TKI, tyrosine kinase inhibitor.…”
Section: Luminal B Subtype Breast Cancer Therapeutic Potentialsmentioning
confidence: 99%
“…Inhibition kinetics of sorafenib on intracellular mitoxantrone (ABCG2 substrate) efflux by ABCG2 was detected as previous described (6). Briefly, HEK293/ABCG2 cells were incubated with mitoxantrone (2.5-20 mmol/L in final) at 37 C for 30 minutes.…”
Section: Drug Accumulation and In Vitro Transport Assaysmentioning
confidence: 99%
“…The intracellular concentration of drug was determined by FACS. The quantity of drug efflux by ABCG2 was calculated by subtracting the values obtained at 37 C from those at 0 C. The inhibitory effect of sorafenib was analyzed using Lineweaver-Burk plots as previously described (6).…”
Section: Drug Accumulation and In Vitro Transport Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many of these inhibitors failed to be utilized in clinical application due to the unacceptable toxicity as well as problematic pharmacokinetic interactions (4). But recently, we have reported that several TKIs, including lapatinib, erlotinib, apatinib, and afatinib, can overcome MDR mediated by ABC transporters (25)(26)(27)(28)(29)(30). And the preliminary results with inhibitors showed no appreciable impacts on cytochrome P4503A4 drug metabolism and no significant drug interactions with common chemotherapeutic agents, offering new hope for combination therapy in cancer patients.…”
Section: Introductionmentioning
confidence: 99%